Extreme Market in Tomohon City: A Study of the Social Interaction - Hasrin, Awaluddin; Sidik, Sangputri; Fathimah, Siti; P, Reski; Syam, Suehartono (ADPEBI, 2022)
Tomohon City in North Sulawesi province is one area famous for having a high tolerance among religious people. Multi-religions inhabit Tomohon City; blending several religions makes Tomohon City have its pattern in building a discourse of religious tolerance. In addition, the interaction between religious people in the city of Tomohon is harmonious. This study explains the interaction between visitors, mainly traders and traders in the Pasar Beriman of Tomohon City. Pasar Beriman, famous as the Pasar extreme, is a social arena that shows the social relations between its visitors and depicts a portrait of religious ties between Muslim and non-muslim communities. This research uses the qualitative descriptive method of collecting data through observation, documentation, and interviews directly with market visitors in Tomohon City. This study's results show that visitors' interaction patterns are integrated and associative. It is illustrated by the interactions that are established. So far, there has never been any conflict or disintegration of traders or market visitors. It is in the form of a positive thing to develop an attitude of tolerance for religious people in the city ofTomohon.